The influence of the Pringle maneuver in laparoscopic hepatectomy: continuous monitor of hemodynamic change can predict the perioperatively physiological reservation - Chen, Yi-Chan; Lee, Min-Hsuan; Hsueh, Shan-Ni; Liu, Chien-Liang; Hui, Chung-Kun; Soong, Ruey-Shyang (Frontiers in Big Data, 2023)
Importance: This is the first study to investigate the correlation between intra-operative hemodynamic change and post-operative hemodynamic status. Objective: Designs, Settings and Participants: Patients receiving laparoscopic hepatectomy were routinely monitored with FloTract for goal direct fluid management. Pringle maneuver was routinely performed during parenchymal dissection and the hemodynamic changes was prospectively recorded. We retrospectively analyze the continuous hemodynamic data from FloTrac to compare the post-operative physiological outcome. Exposures: Pringle maneuver during laparoscopic hepatectomy Main Outcome(s) and Measure(s): Results: Stroke volume variation was not responded to the relief of Pringle maneuver during the first Pringle maneuver predicted the elevated post-operative MELD-Na score. Conclusions and Relevance: The complexity of the hemodynamic data recorded by the FloTrac system during the Pringle Maneuver in laparoscopic hepatectomy can be effectively analyzed by GMM method. The result potentially can predict the risk of short-term liver function deterioration.